Who becomes a politican? - Ernesto Dal Bó; Frederico S. Finan; Olle Folke; Torsten Persson; Johanna Rickne (Research Institute of Industrial Economics (IFN), 2016)
Can a democracy attract competent leaders, while attaining broad representation? Economic models suggest that free-riding incentives and lower opportunity costs give the less competent a comparative advantage at entering political life. Also, if elites have more human capital, selecting on competence may lead to uneven representation. We examine patterns of political selection among the universe of municipal politicians in Sweden using extraordinarily rich data on competence traits and social background for the entire population. We document four new facts: First, politicians are on average significantly smarter and better leaders than the population they represent. Second, the representation of social background, whether measured by intergenerational earnings or social class, is remarkably even. Third, there is at best a weak tradeoff in selection between competence and representation. Fourth, both material and intrinsic motives matter in selection, as does screening by political parties.
Keywords: H10; H70; 330; Political Selection; Political Represenation; Family Background; Competence